Risk factors for perianal abscess recurrence after incision and drainage: a review of the literature - Gabsi, Kheira (International Surgery Journal, 2025)
Perianal abscesses are a commonly managed condition by general surgery, usually with antibiotics and an incision and drainage in the operating theatre. They are estimated to recur 30% of the time. This literature review was performed is to investigate risk factors for recurrence for perianal abscess. The 19 pertinent studies were included, which revealed that inflammatory bowel disease and abscess location have been repeatedly shown to be risk factors for recurrence of perianal abscess. There were numerous other risk factors including diabetes, smoking, patient age and gender, and pre-operative fever that were discussed in the literature but were not consistently between studies shown to be significant.